Kane rules - Mugford , Simon; Green , Dan (London Welbeck, 2020)
Find out how Harry Kane went from east London schoolboy to top premisership scorer, england captain and winner of the 2018 world gup goldden boot
Famous people
Keywords: Biographies; Great Britain; Soccer players